Incomplete and delayed recovery from sudden loss of smell in COVID-19 (Research, Society and Development, 2024)
The research addresses pathophysiological mechanisms, psychosocial impacts, diagnostic methods, therapeutic interventions and factors that influence the recovery of olfactory function. Anosmia in COVID-19 is caused by infection of the support cells in the olfactory epithelium by SARS-CoV-2, resulting in local inflammation and dysfunction of olfactory neurons. The prevalence of anosmia is high, with varying recovery among patients. Diagnostic methods include odor identification tests and self-reports. Therapeutic interventions such as olfactory training and the use of corticosteroids have shown promising results, although effectiveness varies. The psychosocial impact of anosmia is significant, affecting patients' quality of life, mental health and social interactions. The article emphasizes the need for early diagnosis and personalized interventions to improve recovery outcomes. Longitudinal studies and biomarker research are needed to improve therapeutic strategies and better understand recovery mechanisms. It is concluded that anosmia, although often temporary, can be debilitating, requiring ongoing medical and psychological attention.